A KETERAMPILAN BERBICARA SISWA DI SD NEGERI 3 LAPANG KECAMATAN LAPANG KABUPATEN ACEH UTARA DALAM PEMBELAJARAN BAHASA INDONESIA - Rauzatul Jannah; Trisfayani; Syahriandi (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the speaking skills of fifth-grade students at SD Negeri 3 Lapang, Lapang Substrict, North Aceh Regency in Indonesian language learning. The research used a descriptive quantitative approach with instruments including observation, teacher interviews, and students oral tests. The result oral tests. The results showed that acrss seven speaking aspects, most students were in the high category. Pronunciation: 70% high, intonation: 85%, vocabulary mastery: 65%, material mastery: 80%, speaking fluency: 40%, facial ekpression: 85%, and eye contact: 85%. These findings indicate that students’ speaking skills are generally in the good category.